Infralimbic Estradiol Enhances Neuronal Excitability and Facilitates Extinction of Cocaine Seeking in Female Rats via a BDNF/TrkB Mechanism - Yousuf, Hanna; Smies, Chad W.; Hafenbreidel, Madalyn; Tuscher, Jennifer J.; Fortress, Ashley M.; Frick, Karyn M.; Mueller, Devin (Frontiers in Behavioral Neuroscience, 2019)
Women are more susceptible to developing cocaine dependence than men, but paradoxically, are more responsive to treatment. The potent estrogen, 17β-estradiol (E2), mediates these effects by augmenting cocaine seeking but also promoting extinction of cocaine seeking through E2’s memory-enhancing functions. Although we have previously shown that E2 facilitates extinction, the neuroanatomical locus of action and underlying mechanisms are unknown. Here we demonstrate that E2 infused directly into the infralimbic medial prefrontal cortex (IL-mPFC), a region critical for extinction consolidation, enhances extinction of cocaine seeking in ovariectomized (OVX) female rats. Using patch-clamp electrophysiology, we show that E2 may facilitate extinction by potentiating intrinsic excitability of IL-mPFC neurons. Because the mnemonic effects of E2 are known to be regulated by brain-derived neurotrophic factor (BDNF) and its receptor, tropomyosin-related kinase B (TrkB), we examined whether BDNF/TrkB signaling was necessary for E2-induced enhancement of excitability and extinction. We found that E2-mediated increases in excitability of IL-mPFC neurons were abolished by Trk receptor blockade. Moreover, blockade of TrkB signaling impaired E2-facilitated extinction of cocaine seeking in OVX female rats. Thus, E2 enhances IL-mPFC neuronal excitability in a TrkB-dependent manner to support extinction of cocaine seeking. Our findings suggest that pharmacological enhancement of E2 or BDNF/TrkB signaling during extinction-based therapies would improve therapeutic outcome in cocaine-addicted women.